A Multimodal Analysis of Advertisements Broadcasted on YouTube Based on Gender - Khairunnisa, Syafira; Rosita, Nur (English Language and Literature, 2024)
This research is concerned with the multimodal analysis of advertisements broadcasted on YouTube based on gender. This study focused on Rexona men and women advertisements in order to analyze gender stereotypes portrayed in verbal and visual elements from the advertisements. A qualitative method was used to analyze the data in the study. Visual data were analyzed by transitivity theory by Halliday (2004), visual data were analyzed by visual grammar representation (Kress and van Leeuwen, 2006) and generic structure potential (Cheong, 2004). Meanwhile, gender stereotypes were analyzed by Branndon (2017) aspect of gender stereotype theory. The result showed that from all six types of processes, material process is the dominant process of the verbal element of Rexona men and women advertisement, whereas in visual grammar analysis dominated by action process. In addition, visual analysis is dominated by visual elements such as lead, display, and emblem. Gender stereotypes could be seen in Rexona Women's advertisement because personality traits dominate it. In contrast, domestic behavior and occupation often appeared in Rexona men's advertisements.